Beyond the banking hall - Dangogo, Kabir (Kaduna, Nigeria: Timex Communications, 2008)
The books explains the image management of a bank, the role of public relations in banking.
Includes bibliographic references and index.
oif 29/07/2020
Loans
Keywords: Banks and banking; Public relations